IMPLEMENTASI ALGORITMA FOLD-GROWTH UNTUK MENEMUKAN POLA KELULUSAN MAHASISWA - Muhammad Hasbi Assidiqqi; Alwis Nazir; Iwan Iskandar; Jasril Jasril; Fitri Insani (TEKTRIKA, 2022)
Timely graduation of students is important for a study program and higher education institution. According to BAN-PT Regulation Number 23 of 2022 concerning Instruments for Monitoring and Evaluation of Higher Education Accreditation Ratings, the ideal percentage of student graduation on time is ? 37.5% for academic tertiary institutions and ? 47.5% for vocational tertiary institutions. The timely graduation of Informatics Engineering Study Program students at UIN Sultan Syarif Kasim Riau every year is still below the standards set by BAN-PT. In 2021 the number of students who graduate on time is only 12%. By using student data in the form of acceptance and graduation data in the form of length of study and GPA, excavation of graduation patterns is carried out using the FOLD-Growth algorithm. The FOLD-Growth algorithm is a combined algorithm of FOLDARM and FP-Growth. With 274 student data, a minimum support value of 20%, and a minimum confidence of 50%, it produces two patterns with the strongest lift ratio value of 3.61, while with a minimum support of 10% and a minimum confidence of 50%, it produces three patterns. with the strongest lift ratio of 7.03. The results of this study can be used as a guideline for increasing student graduation rates on time, by providing a larger intake quota for new students on a pathway that results in on-time graduation, so that it will increase student graduation on time. Key Words: Student graduation, Association Rule, lift ratio, FOLD-Growth, FP-Growth